Gait Parameters and Fall Risk Among Older Adults in Tabanan Regency - Dewi, Ni Putu Indira Prana; Wirata, Gede; Sudiman, Jaqueline; Muliani (Babali Nursing Research, 2026)
Introduction: Fall risk is a major geriatric concern linked to age-related gait instability. Changes in gait parameters, such as step length, step width, and walking speed, reflect neuromuscular decline and increase instability. While international evidence supports this association, local data among community-dwelling older adults in Tabanan Regency, Bali, remain limited. This study aimed to examine the association between gait parameters and fall risk.Methods: This cross-sectional observational study included 119 community-dwelling adults aged 60–79 years. Gait parameters, including step length, step width, and walking speed, were assessed using the 10-meter walk test, and fall risk was measured using the Timed Up and Go (TUG) test. Chi-square tests were used for bivariate analysis, and binary logistic regression was used to identify independent predictors.Results: A total of 36.1% of participants were classified as at risk of falling. Bivariate analysis showed significant associations between fall risk and step length (p = 0.050), step width (p = 0.006), walking speed (p < 0.001), and age (p < 0.001). Multivariate analysis identified walking speed (AOR = 0.150; p = 0.005), leg-length symmetry (AOR = 0.292; p = 0.026), and step width (AOR = 0.345; p = 0.038) as independent predictors. Step length was excluded from the multivariate analysis due to complete separation in the data.Conclusion: Walking speed, step width, and leg-length symmetry were independent predictors of fall risk. These findings support the use of simple gait assessments for early fall risk screening in community and primary care settings.